Mechanisms of Effector-Mediated Immunity Revealed by the Accidental Human Pathogen Legionella pneumophila - Ngwaga, Tshegofatso; Chauhan, Deepika; Shames, Stephanie R. (Frontiers in Cellular and Infection Microbiology, 2021)
Many Gram-negative bacterial pathogens employ translocated virulence factors, termed effector proteins, to facilitate their parasitism of host cells and evade host anti-microbial defenses. However, eukaryotes have evolved to detect effector-mediated virulence strategies through a phenomenon termed effector-triggered immunity (ETI). Although ETI was discovered in plants, a growing body of literature demonstrates that metazoans also utilize effector-mediated immunity to detect and clear bacterial pathogens. This Mini Review is focused on mechanisms of effector-mediated immune responses by the accidental human pathogen Legionella pneumophila. We highlight recent advancements in the field and discuss the future prospects of harnessing effectors for the development of novel therapeutics, a critical need due to the prevalence and rapid spread of antibiotic resistance.